Adding concurrent chemotherapy to postoperative radiotherapy improves locoregional control but Not overall survival in patients with salivary gland adenoid cystic carcinoma—a propensity score matched study. Issue 1 (December 2016) - Hsieh, Cheng-En; Lin, Chien-Yu; Lee, Li-Yu; Yang, Lan-Yan; Wang, Chun-Chieh; Wang, Hung-Ming; Chang, Joseph; Fan, Kang-Hsing; Liao, Chun-Ta; Yen, Tzu-Chen; Fang, Ku-Hao; Tsang, Yan-Ming
Abstract Purpose To compare the long-term outcomes in patients with salivary gland adenoid cystic carcinoma (SGACC) treated with post-operative chemoradiotherapy (POCRT)versus post-operative radiotherapy (PORT). Methods We retrospectively reviewed the records of 91 SGACC patients treated with surgery followed by PORT (n  = 58) or POCRT (n  = 33) between 2000 and 2013. Treatment outcomes between groups were compared using propensity score matching (1:1 nearest neighbor). Results The median radiation dose was 66 Gy, and patients were followed up for a median of 71 months. Cisplatin-based concurrent regimens were the most commonly used chemotherapy schedules. In the entire study cohort, patients undergoing POCRT showed a trend toward higher locoregional control (LRC) rates than those treated with PORT alone at both 5 and 8 years (97 and 97 %versus 84 and 79 %, respectively;P  = .066). Distant metastases were the most common form of treatment failure and occurred in 31 (34 %) patients (PORT, n  = 17; POCRT, n  = 14). After propensity score matching (33 pairs), patients receiving POCRT had 5- and 8 year LRC rates of 97 and 97 %, respectively, compared with 79 and 67 % for patients treated with PORT alone (P  = .017). The two groups did not differ significantly in terms of distant metastasis-free survival (DMFS), disease-free survival (DFS), and overall survival (OS). However, a significantly better opioid-requiring pain-free survival (ORPFS) was achieved in POCRT group (P  = .038). Subgroup analyses revealed that patients with stage III − IV disease (P  = .040 and .017), positive surgical margins (P  = .011 and .050), or perineural invasion (P  = .013 and .035) had significantly higher 5- and 8 year LRC and ORPFS when treated with POCRT, respectively. Conclusions In SGACC patients, adding concurrent chemotherapy to PORT may increase LRC and ORPFS rates, particularly in presence of stage III − IV disease, positive surgical margins, or perineural invasion. However, no significant differences in DMFS, DFS, and OS were observed.